2019
DOI: 10.3390/pr7110861
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Toxicity of Natural Oils from Mentha piperita, Pinus roxburghii, and Rosa spp. Against Three Stored Product Insects

Abstract: Three natural oils extracted from Mentha piperita, Pinus roxburghii, and Rosa spp. were assessed in order to determine their insecticidal activity against the adults of three stored product insects: the rice weevil (Sitophilus oryzae L.), the lesser grain borer (Rhyzopertha dominica, Fabricius), and the red flour beetle (Tribolium castaneum, Herbst.). By Gas chromatography–mass spectrometry (GC/MS) analysis, the main compounds in the n-hexane oil from Rosa spp. were determined to be methyl eugenol (52.17%), ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…Recently, some EOs have been reported to be effective in reducing decay, in quality maintenance and in the essential improvement of post-harvest life of many fruits (grape, strawberry, blueberry, raspberry, blackberry and fresh-cut fruit) [17]. In particular, aldehydes, phenols and ketones considerably inhibit pathogen growth [18][19][20][21][22]. Thymol, carvacrol and p-anisaldehyde have proven fungicidal activity and the EO rich in these components showed the highest inhibitory activity against many post-harvest pathogens, such as Botrytis spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some EOs have been reported to be effective in reducing decay, in quality maintenance and in the essential improvement of post-harvest life of many fruits (grape, strawberry, blueberry, raspberry, blackberry and fresh-cut fruit) [17]. In particular, aldehydes, phenols and ketones considerably inhibit pathogen growth [18][19][20][21][22]. Thymol, carvacrol and p-anisaldehyde have proven fungicidal activity and the EO rich in these components showed the highest inhibitory activity against many post-harvest pathogens, such as Botrytis spp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various plant materials are being used as pesticides (insecticides). Mackled et al [ 39 ] found that the essential oils of Mentha piperita , Pinus roxburghii , and Rosa spp. were highly effective against some stored product pests.…”
Section: Discussionmentioning
confidence: 99%
“…The photochemical analysis of leaf crude oil was performed on GC-MS which resulted in the identification of a total of 43 major components with different retention time. The identified compounds and their relative contents are listed in Tables 2 to 4 and Figure 2(a) to (c). The percentage peak area was taken as percentage composition of the constituents.…”
Section: Chemical Composition Identificationmentioning
confidence: 99%
“…However, it suffers major economic loss caused by grain infesting insect. The cumulative effects of feeding, breeding, transmission of toxic, saprophytic fungi, and associated changes in the microecological conditions in the grain bulk 4 cause deterioration process in the grain. 1,5 It has been estimated that about 15-20% of Ethiopian stored grain agricultural product is lost every year due to weevil infestation.…”
Section: Introductionmentioning
confidence: 99%